Interleukin-17 mediated immunity during infections with Trypanosoma cruzi and other protozoans - Vesely, María Carolina Amezcua (Biochim Biophys Acta Mol Basis Dis, 2020)
Host resistance during infection with Trypanosoma cruzi, and other protozoans, is dependent on a balanced immune response. Robust immunity against these pathogens requires of the concerted action of many innate and adaptive cell populations including macrophages, neutrophils, dendritic cells, CD4(+), and CD8(+) T cells and B cells among others. Indeed, during most protozoan infections only a balanced production of inflammatory (T(H)1) and anti-inflammatory (T(H)2/regulatory) cytokines will allow the control of parasite spreading without compromising host tissue integrity. The description of T(H)17 cells, a novel effector helper T cell lineage that produced IL-17 as signature cytokine, prompted the revision of our knowledge about the mechanisms that mediate protection and immunopathology during protozoan infections. In this manuscript we discuss the general features of IL-17 mediated immune responses as well as the cellular sources, effector mechanisms and overall role of IL-17 in the immune response to T. cruzi and other protozoan infections.